Simulium (asiosimulium) furvum, a new species of black fly (diptera: Simuliidae) from Thailand - Takaoka H. (2014)
Simulium (Asiosimulium) furvum sp. nov. (Diptera: Simuliidae) is described from female, male, pupal, and larval specimens collected from Maewa National Park, Lampang Province, Thailand. This new species represents the fourth member of the subgenus Asiosimulium Takaoka & Chochoote, one of two small black fly subgenera endemic in the Oriental Region. It is characterized by a pear-shaped spermatheca in the female; a ventral plate in the male with a laterally compressed median keel directed ventrally and with a deep notch posteromedially, and aedeagal membrane with stout spines; and by 22 gill filaments in the pupa. Taxonomic notes are provided to separate this new species from three known species, Simulium (Asiosimulium) oblongum Takaoka & Choochote and Simulium (Asiosimulium) wanchaii Takaoka & Choochote, both from Thailand, and Simulium (Asiosimulium) suchitrae Takaoka from Nepal. © 2013 Entomological Society of America.